Frequency of Radiologically Confirmed Pneumonia in Children with First Time Wheezing at Pediatric Emergency Department, Liaquat University Hospital Hyderabad (Medical Forum Monthly, 2024)
Objective: To assess the frequency of radiologically confirmed pneumonia in children with first time wheezing at pediatric emergency department, Liaquat University Hospital Hyderabad. Study Design: Descriptive Cross Sectional Study Place and Duration of Study: This study was conducted at the at Department of Pediatric Liaquat University Hospital, Hyderabad from January to June 2017. Materials and Methods: A Descriptive Cross Sectional Study was conducted at Department of Pediatric Liaquat University Hospital, Hyderabad, total six months’ duration from 1st January to 30 June 2017. The child who came first time with wheeze with signs of fast breathing and chest in drawing as per operational definition were nebulized with rapid acting inhaled bronchodilator i.e. Ventolin solution upto three times 20 minutes apart. According to standard/IMNCI protocol soon after three times nebulization, they were reassessed for persistence of fast breathing and chest indrawing and reclassified as Pneumonia if fast breathing and/or chest indrawing persisted. The chest radiography was done in all of the children to confirm the radiological finding suggestive of pneumonia. Results: Mean ± SD of age was 21.13±12.06 with C.I (19.02-23.24) months. Mean ± SD of duration of symptoms was 2.34±1.11 with C.I (2.15-2.54) days. Out of 128 patients 67 (52.3%) were male and 61 (47.7%) were female. Radiologically proven Pneumonia was present in 54 (42.2%) patients. Conclusion: Our study shows that out of 128 children who presented with first time wheeze; 42.2% had radiologically proven pneumonia while 57.8% did not have radiological findings of pneumonia. Boys had higher proportion of pneumonia than girls. Based on our study findings, it is suggested that all children who present first time with wheeze and signs of fast breathing and chest indrawing should be screened for pneumonia.